PENGARUH VARIASI PERSENTASE EKSTRAK JANGKRIK (Gryllus sp Walk) YANG BERBEDA TERHADAP TINGKAT SURVIVAL RATE BENIH IKAN MAS KOKI (Carrasius auratus L) - Elrifadah Elrifadah; Yulius Kisworo (Universitas Lambung Mangkurat, 2013)
This study Aims to Determine the effect of different variations on survival seed cicada goldfish. The method used in this study is completely randomized design with 3 treatments (A = 3%, B = 5%, and C = 7%) and three replications. From these results Obtained survival rate to 83.0% Obtained treatment A, B Obtained 88.33% and 80.0% Obtained C treatment. Then the results of analysis of variance accept the hypothesis Ho that the percentage variation of different cicada extract (3%, 5% and 7%) did not Affect the survival rate of seedlings goldfish. During the last condition of water quality research support for seed viability parameters goldfish.